Perkembangan Makna Milk al-Yamīn - Muhammad Ulinnuha; Nur Hamidah Arifah (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2020)
Although the slavery system has been eliminated from the world order, the practice can still be found in other forms, such as human trafficking or the sale of women as illegal workers through online applications. The Qur’an responds to the practice of slavery in various terms. One of them is milk al-yamīn. It is important to study the concept of milk al-yamīn by reading the diachronic-chronological history. In order to know the dimensions of continuity, change, and development of meaning from the classical to the contemporary period. This study examines four interpretations, each representing a different period. Classical interpretation is represented by Tafsir aṭ-Ṭabarī, the middle period is represented by Tafsir al-Qurṭubī, the modern era is represented by Fī Zhilāl Al-Qur’ān, and the contemporary era is represented by Tafsir al-Munīr. This research shows that the interpretation of milk al-yamin in the classical and medieval era tends to be the same. Then underwent a change in meaning in the modern and contemporary period.